Pengetahuan Pelabelan Produsen Industri Rumah Tangga Pangan di Kota Bogor - Jian Septian; Winiati Pudji Rahayu (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2014)
Labeling is an important part of food packaging that must comply to the labeling regulation. The objective of this research was to evaluate the knowledge of Small-Medium Enterprises (SMEs) in food labeling regulation and their compliance . The research was conducted by surveying 88 SMEs operating in Bogor as respondents and evaluating their food product labels. More than 55 % food labels comply to the labeling regulation but only 16 % of SMEs producers understood well about the food labeling regulation. Fifty percent of respondents obtained information on food labeling regulation from Indonesian Health District Of ce. The results of spearman correlation test showed that the correlation between SMEs producers characteristics (age, education, occupation, and socio-economic status) were not significant (p>0.05) with their perception regarding food labeling.